2016
DOI: 10.1016/j.ijpe.2016.03.014
|View full text |Cite
|
Sign up to set email alerts
|

Big data analytics in logistics and supply chain management: Certain investigations for research and applications

Abstract: The amount of data produced and communicated over the Internet is significantly increasing, thereby creating challenges for the organizations that would like to reap the benefits from analyzing this massive influx of big data. This is because big data can provide unique insights into, inter alia, market trends, customer buying patterns, and maintenance cycles, as well as into ways of lowering costs and enabling more targeted business decisions. Realizing the importance of big data business analytics (BDBA), we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
863
0
18

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 1,109 publications
(892 citation statements)
references
References 139 publications
11
863
0
18
Order By: Relevance
“…There are also other researches that amplified the collaboration benefits (Zhao et al, 2016;Bosona & Gebresenbet, 2011;Kim et al, 2015;Wang et al, 2016). The collaboration approach is based on a theoretical aspect of improvement of the efficiency of the chain, e. g., partial freight collection, information sharing, etc.…”
Section: Supply Chain Resilience Concept and Capabilitiesmentioning
confidence: 99%
See 3 more Smart Citations
“…There are also other researches that amplified the collaboration benefits (Zhao et al, 2016;Bosona & Gebresenbet, 2011;Kim et al, 2015;Wang et al, 2016). The collaboration approach is based on a theoretical aspect of improvement of the efficiency of the chain, e. g., partial freight collection, information sharing, etc.…”
Section: Supply Chain Resilience Concept and Capabilitiesmentioning
confidence: 99%
“…However, they did not consider collaboration and resilience aspects. Wang et al (2016) Goncalves & Chicareli (2014) identified capabilities that make the largest contribution to resilience flexibility (supplier, product, process, transportation), collaboration (information sharing, joined decision making, working together), structure of chain (physical, information), and agility (visibility, velocity). Goncalves and Chiricareli amplifies that empirical studies about most suitable management capabilities before, during a after a distribution in the supply chain is needed.…”
Section: Supply Chain Resilience Concept and Capabilitiesmentioning
confidence: 99%
See 2 more Smart Citations
“…The initial search for articles connecting Big Data with operations models was conducted using the Scopus database 1 , identifying 668 articles. As suggested by Wang et al, (2016) we then intuitively checked through all the titles and only included those articles in which: "big data technologies were not only considered as possible new tools for enterprise operation, but which were also triggering impacts in the management (operations and supply chain management) arena" (p. 98). This resulted in 200 articles which were retained for further analysis.…”
Section: Contextualising Big Datamentioning
confidence: 99%